ANALISIS KEBUTUHAN PENGEMBANGAN SISTEM INFORMASI RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH BANYUMAS: ANALISIS KEBUTUHAN PENGEMBANGAN SISTEM INFORMASI RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH BANYUMAS - Zahrasita Nur Indira; Aris Puji Widodo; Farid Agushybana (Yakpermas Press, 2023)
A hospital is a place that provides health services which include observation, diagnostic, therapeutic, and rehabilitation activities for patients. Development of information systems using Prototype. To support the development of the information system, the PIECES framework is used, which is seen in terms of performance, information, economics, control, efficiency, and service. One part of the service at RSUD Banyumas that has used a management information system is an outpatient installation. However, the clinical pathway audit process has not been carried out in the outpatient department, so it cannot measure the quality of services provided by doctors and cannot be done in decision and policy making. This type of research is qualitative. The management of clinical pathway data audits still uses a manual system and does not optimize computerized data processing. Based on the results of the research that has been carried out, the following conclusions were obtained Outpatient information system at RSUD Banyumas so far, there are problems with the process carried out manually related to the management of Clinical Pathway audits. There needs to be an integrated information system to the hospital management to facilitate access to the information needed.